The case for integrating public health informatics networks. - Snee, N.L.
Our public health future depends on information technology (IT). Our nation's capability to respond to natural disasters and those caused by bioterrorists require an integrated information architecture that is well planned. Enterprise architectures have not routinely been planned. Stovepipes have been built and "band-aid" software has been holding different hardware designs together. Engineering challenges abound in our solutions to an IT environment that links individual health data with population data. These goals are achievable with blueprints like the PHIN for technical requirements, state-of-the-art standards like those recommended by the U.S. Department of Health and Human Services (HHS) and the e-Health initiative. The engineering designs require rational, modular, verifiable, and reusable components in an integrated environment.
Keywords: Bioterrorism; e-Health initiative; Enterprise information infrastructure; Integrated environment; Knowledge management; Patient information; Public health future; Public health informatics networks; Requirements analysis